2022
DOI: 10.3390/jcm11195748
|View full text |Cite
|
Sign up to set email alerts
|

Classification und Treatment Algorithm of Small Bowel Perforations Based on a Ten-Year Retrospective Analysis

Abstract: Background: Small bowel perforations are a rare diagnosis compared with esophageal, gastric, and colonic perforations. However, small bowel perforations can be fatal if left untreated. A classification of small bowel perforations or treatment recommendations do not exist to date. Methods: A retrospective, monocentric, code-related data analysis of patients with small bowel perforations was performed for the period of 2010 to 2019. Results: Over a 10-year period, 267 cases of small bowel perforation in 257 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Regarding gender, our results (Table 1) show that there is a higher prevalence of traumatic bowel perforation in males (87.5%), which is comparable to the results of a study by Onken et al (2022), which indicated that 50.2% of participants with small bowel perforation were males while 49.8% of participants were females [7].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding gender, our results (Table 1) show that there is a higher prevalence of traumatic bowel perforation in males (87.5%), which is comparable to the results of a study by Onken et al (2022), which indicated that 50.2% of participants with small bowel perforation were males while 49.8% of participants were females [7].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding gender, our results (Table 1 ) show that there is a higher prevalence of traumatic bowel perforation in males (87.5%), which is comparable to the results of a study by Onken et al (2022), which indicated that 50.2% of participants with small bowel perforation were males while 49.8% of participants were females [ 7 ]. Our results are also comparable to the findings of a study by Mukhopadhyay et al (2009), which showed that the male-to-female ratio for traumatic bowel injury from blunt abdominal trauma was 8.4: 1 [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Common CT findings of duodenal FB perforation include localized mesenteric fatty infiltration, focal thickening of the bowel wall and pelvic effusion 24 . Free pneumoperitoneum is rare, as the FB is gradually impacted and the perforation is locally covered with fibrin or omentum 24–26 . In addition, endoscopy can be used as a diagnostic tool, as well as for treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Free pneumoperitoneum is rare, as the FB is gradually impacted and the perforation is locally covered with fibrin or omentum. 24 , 25 , 26 In addition, endoscopy can be used as a diagnostic tool, as well as for treatment.…”
Section: Discussionmentioning
confidence: 99%